2012
DOI: 10.1111/j.1365-2222.2012.04032.x
|View full text |Cite
|
Sign up to set email alerts
|

Pets at birth do not increase allergic disease in at‐risk children

Abstract: Pets at birth either decreased or had no effect on allergic disease up to age 12. We found no evidence that exposure to cats or dogs at birth increases the risk of allergic disease in high-risk children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 50 publications
2
23
0
2
Order By: Relevance
“…We did not detect any differences between children with recurrent wheezing or asthma with respect to the presence of domestic pets, particularly cats and dogs. This result appeared to exclude an effect of pet ownership on respiratory symptoms and was consistent with some previous findings [36]. However, it has been reported that exposure to cats during the first year of life is an independent risk factor for wheezing and asthma at the age of 7 years [37].…”
Section: Discussionsupporting
confidence: 91%
“…We did not detect any differences between children with recurrent wheezing or asthma with respect to the presence of domestic pets, particularly cats and dogs. This result appeared to exclude an effect of pet ownership on respiratory symptoms and was consistent with some previous findings [36]. However, it has been reported that exposure to cats during the first year of life is an independent risk factor for wheezing and asthma at the age of 7 years [37].…”
Section: Discussionsupporting
confidence: 91%
“…In the same way poverty is linked with poor hygienic conditions. This might explain why our as well as other Latin American studies have shown lack of hygiene [12,40,51], exposure to farm animals [52] and pets [53] as risk factors for asthma and allergies while other studies – mainly European studies [54-56] – have indicated an inverse relationship between low level of hygiene and such diseases. Our findings cast doubts on whether differences in phenotype of asthma, rhinoconjunctivitis and eczema in Latin America [57-59] are really the main reason for the dissimilarity with prevalence in other parts of the world [60].…”
Section: Discussionmentioning
confidence: 82%
“…Following the original report from Hesselmar and Bjorksten in 1998 that children raised in a house with a cat were less likely to be allergic to cats, there have been extensive publications related to this phenomenon (17, 32, 33). Many reports have confirmed the original observation, but with significant differences between the effects of cat and dog ownership (18, 20, 34).…”
Section: Discussionmentioning
confidence: 99%